The Assessment of Channel Bonding and Aggregation on WLANs - Amiteshwar Bhalavi, Sanjiv Tokekar ,Ankit Saxena (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To improve throughput IEEE 802.11ac is one of the newest variants of WLANs that use modulation and coding schemes (MCS), channel bonding, and frame aggregation. Channel Bonding permits wireless appliances to work at 40 MHz channels with replicating their bandwidth from standard 20 MHz channels in a 5 GHz band. With the increase in channel width, data rate is improved but non-overlapping channels decreased. Frame integration allows concatenation and posting of multiple frames within a single channel. In this paper, we have analyzed the throughput in two scenarios, Channel bonding as well as aggregation with Channel Bonding. The simulation results confirm that the channel bonding performs superior to aggregation with Channel Bonding in terms of throughput.